2004
DOI: 10.1111/j.1559-1816.2004.tb02794.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Type and Level of Personal Involvement on Information Search and Problem Solving1

Abstract: The effects of type and level of personal involvement on information search and problem solving were investigated in a laboratory setting. Participants were given a problem eliciting high value involvement, high outcome involvement, or low involvement. Before providing a solution to the problem, participants had the opportunity to search for additional information about the problem using a computer. The amount of information searched and the time spent searching were measured, as was the quality of problem sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 37 publications
1
33
0
Order By: Relevance
“…The potential mediating effect of problem construction between values and destructive problem solving also needs further exploration. Illies and Reiter-Palmon (2004) revealed that problems that activate powerful values in participants could have a closed-minded effect, decreasing the quality of solutions generated to those problems. However, we still do not know exactly why, how, or where this effect occurs and if it plays a specific role in destructive problem solving.…”
Section: Limitations and Future Directionsmentioning
confidence: 97%
“…The potential mediating effect of problem construction between values and destructive problem solving also needs further exploration. Illies and Reiter-Palmon (2004) revealed that problems that activate powerful values in participants could have a closed-minded effect, decreasing the quality of solutions generated to those problems. However, we still do not know exactly why, how, or where this effect occurs and if it plays a specific role in destructive problem solving.…”
Section: Limitations and Future Directionsmentioning
confidence: 97%
“…This prevents individual learners' sense of detachment, while maintaining their focus on the learning facets of the experience (Illies & Reiter-Palmon, 2004). Therefore, a group learning process can serve as a mechanism that enables absorbed individuals to channel their high levels of cognitive energy into an effective learning experience.…”
Section: The Role Of Cognitive Absorption In Collaborative Learningmentioning
confidence: 99%
“…(Humphreys MS, Revelle W. 1984). Illies and Palmon (2004) however, found that when people search and find information, which may confront their values, then motivation tend to be a negative predictor of the information seeking performance. • People having good flow, defined as "a balance state between '"skill"' and '"challenge"' (Csikszentmihalyi M. 1990) with characteristics such as : clear goal, feedback, concentration, focus, control, loss of selfconsciousness, transformation of time, and autotelic nature (Csikszentmihalyi M. 1997), aids performance.…”
Section: Personal Dimensions From the Fields Of Psychology And Informmentioning
confidence: 96%